2019
DOI: 10.1111/jfpp.14276
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ozone processing on microbiological, physicochemical, and bioactive characteristics of refrigerated stored Cantaloupe melon juice

Abstract: The objective of this study was to evaluate the impact of ozone treatment on microbiological decontamination (intrinsic microflora and inoculated Listeria innocua) and some physicochemical characteristics and bioactive compounds of Cantaloupe melon juice, also during refrigerated storage. To determine adequate ozone exposure, the survival curve of L. innocua was previously assessed. A thermal treatment was also performed seeking comparison with ozone treatment impact. After ozone exposure, L. innocua was not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…During storage, browning increased in cantaloupe juice, due to the development of brown pigment over polymerization between ascorbic acid or sugar degradation products or phenolic compounds (Wibowo et al, 2015) [33] . A similar decrease in vitamin was found in a refrigerated stored cantaloupe juice stored at (5±2 C) for 13 days by Sroy et al (2019) [29] . The same previous order in terms of preference for vitamin C and reduced browning is of the same order obtained by L*, a*, b*, hue, and chroma parameters.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…During storage, browning increased in cantaloupe juice, due to the development of brown pigment over polymerization between ascorbic acid or sugar degradation products or phenolic compounds (Wibowo et al, 2015) [33] . A similar decrease in vitamin was found in a refrigerated stored cantaloupe juice stored at (5±2 C) for 13 days by Sroy et al (2019) [29] . The same previous order in terms of preference for vitamin C and reduced browning is of the same order obtained by L*, a*, b*, hue, and chroma parameters.…”
Section: Discussionsupporting
confidence: 80%
“…The pattern of our results was close to that observed by Tahar et al (2019) [30] in pasteurized pear juice and orange juice. The degradation in vitamins, polyphenols, and carotenoids during storage decreased antioxidant activity in juices (Sroy et al, 2019) [29] . Although cantaloupe juice is not high in phenolic content but contains a higher percentage of Hydroxylated cinnamic acids than Hydroxybenzoic acid derivatives, which are more antioxidant activity than Hydroxybenzoic acid derivatives due to their esters have more hydroxyl in the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of pulsed light (PL) treatment conditions on the Vitamin C content in Indian gooseberry (amla) juice was explored, and the results showed that a 61% better retention was obtained in comparison to the thermally pasteurised counterpart [80]. Similarly, the positive effect of the ozone treatment when compared to traditional pasteurisation was shown by Sroy et al 2019 [81], who studied Vitamin C behaviour in cantaloupe melon juice immediately after treatment but, also, during refrigerated storage.…”
Section: Effect Of Nonthermal Processes On Vitamin C Retentionmentioning
confidence: 99%
“…Fenoles totales 182.27 ug EAG/mL 54 Ácido ascórbico 23.84 mg AA/100 mL 54 bs: base seca; EAG: Equivalentes de Ácido Gálico; EC: Equivalentes de Catequinas; EQ: Equivalentes de Quercetina; AA: Ácido ascórbico.…”
Section: Melónunclassified